2005
DOI: 10.1037/0021-843x.114.4.612
|View full text |Cite
|
Sign up to set email alerts
|

Conjoint Developmental Trajectories of Young Adult Alcohol and Tobacco Use.

Abstract: Developmental and etiological advances have set the stage for considering trajectories of problem behavior across the life course, but little work thus far addresses co-occurring problem behavior trajectories. Although recent work characterizes drinking and smoking trajectories, none has explored the course of concurrent drinking and smoking. Using panel data from the Monitoring the Future Project (N = 32,087), the authors applied growth mixture modeling to 4 waves of heavy drinking and smoking in a young-adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 71 publications
1
80
0
1
Order By: Relevance
“…The advantages of this approach include the abilities to draw meaningful distinctions among the groups in terms of antecedents and consequences and to consider the occurrence of similar trajectory groups across different outcomes. 77 Maggs and Schulenberg 74 summarized several studies that used this approach to examine alcohol use and problem drinking during late adolescence and early adulthood. Although the studies varied considerably in terms of ages, waves, measures, and analytic strategies, several common trajectory groups were found across the studies (Table 3).…”
Section: Trajectories Of Alcohol Use and Problem Drinking Over Timementioning
confidence: 99%
“…The advantages of this approach include the abilities to draw meaningful distinctions among the groups in terms of antecedents and consequences and to consider the occurrence of similar trajectory groups across different outcomes. 77 Maggs and Schulenberg 74 summarized several studies that used this approach to examine alcohol use and problem drinking during late adolescence and early adulthood. Although the studies varied considerably in terms of ages, waves, measures, and analytic strategies, several common trajectory groups were found across the studies (Table 3).…”
Section: Trajectories Of Alcohol Use and Problem Drinking Over Timementioning
confidence: 99%
“…Virtually all studies have found male gender to be associated with higher baseline levels of heavy drinking and trajectories more indicative of increasing or continued heavy drinking. Other factors associated with change in drinking behavior over time have included baseline levels of alcohol and other substance use (Auerbach and Collins, 2006;Chassin et al, 2002;Hill et al, 2000;Sher and Rutledge, 2007;Windle et al, 2005); family history of alcoholism (Chassin et al, 2002(Chassin et al, , 2004Jackson et al, 2001;Timberlake et al, 2007); borderline personality disorder (PD) and/or behavioral undercontrol and impulsivity (Rohde et al, 2001;Rutledge and Sher, 2001); externalizing behavior, delinquency, conduct disorder, and antisocial PD (Bucholz et al, 2000;Chassin et al, 2002;Hill et al, 2000;Jackson and Sher, 2005;Tucker et al, 2003); and early initiation of drinking (Casswell et al, 2002;Goudriaan et al, 2007;Windle et al, 2005).…”
Section: Three-year Changes In Adult Risk Drinking Behavior Inmentioning
confidence: 99%
“…Covariates were mean centered to enhance interpretability of coefficients (Aiken & West, 1991). For the current study, one to four class models were compared by using the BIC, classification accuracy, class prevalence greater than 5% of sample (Jackson, Sher, & Schulenberg, 2005), the Lo-Mendell-Rubin likelihood ratio test (LRT) for k versus k -1 classes (Lo, Mendell, & Rubin, 2001), class interpretability and inspection of pseudoclass plots for all classes to check the scatter of observations. Classification accuracy was measured by using the entropy statistic measure given by Ramasway, DeSarbo, Reibstein, and Robinson (1993), with entropy values close to 1 (range = 0 to 1), indicating higher classification precision.…”
mentioning
confidence: 99%